Problematika Asas kebebasan Berkontrak dalam Perancangan Kontrak Jual Beli: Telaah terhadap Posisi Tawar Para Pihak - Nita Ayuningsih; Mokhamad Fajar Zihady Faturrahman; Vania Aulia; Rayi Kharisma Rajib (Lembaga Pengembangan Kinerja Dosen, 2025)
The strong bargaining power imbalance in the formation of sales contracts, particularly in standard contracts unilaterally drafted by business actors, undermines the principle of freedom of contract, as it is not accompanied by the principle of balance that should ensure a proportional distribution of rights and obligations. This study aims to identify legal issues arising from such imbalances and examine how the principle of balance can be effectively implemented to achieve contractual justice. Using a normative juridical method and conceptual, statutory, and comparative approaches, the research finds that exoneration clauses, unilateral clauses, and “take it or leave it” practices are the primary causes of the loss of substantive consensus in standard contracts. The findings indicate that existing legal protections are still insufficient to prevent the dominance of business actors an issue increasingly evident in the rapidly growing digital sector. The study highlights the need for stronger supervisory instruments, greater transparency in contract drafting, and the reformulation of standard clauses to better reflect proportionality. It also opens opportunities for further empirical research to assess the effectiveness of applying the principle of balance in everyday contractual practices.